Acylethynylpyrroles as a platform for the one-pot access to 2-(pyrrol-2-yl)-3-acylpyridines via the dihydrogenative annelation with propargylamine. Issue 45 (7th November 2018) - Sobenina, Lyubov' N.; Sagitova, Elena F.; Markova, Marina V.; Ushakov, Igor' A.; Ivanov, Andrey V.; Trofimov, Boris A.
Graphical abstract: Highlights: Transition metal-free cross-coupling of pyrroles with acyl(bromo)acetylenes in a solid Al2 O3 medium. Addition of propargylamine to acylethynylpyrroles. One-put synthesis of pyrrolyl-pyridines from acylethynylpyrroles and propargylamine. Abstract: Acylethynylpyrroles, available via the transition metal-free coupling of pyrroles with acylhaloacetylenes are readily annelated with propargylamine in a one-pot step-wise procedure: catalyst-free heating (60–65 °C, 6–16 h) in DMSO and then keeping for 2.5 h with CuI at the same temperature. The products are pyrrolyl-pyridines isolated in good to excellent yields (56–94%). It is experimentally shown that dehydrogenation of intermediate dihydropyridine moiety is not resulted from the oxidation with DMSO (Me2 S was not detected) or air (argon blanket) and is likely associated with the CuI catalysis.